Self, Free Will and Compassion: Shared Constructs in Neuroscience and Buddhism - Jaeger, Dieter; Gonpo, Lobsang (Frontiers in Communication, 2021)
The authors, a neuroscientist and a Buddhist monastic who met through the Emory Tibet Science Initiative, highlight similarities in the understanding of mental activities found in both traditions. An important principle discovered is the parallel processing of multiple mental activities, which reveals the existence of a unitary self and free will as illusions. These insights provide the rationale in Buddhism to develop a culture of compassion. Meanwhile western psychology and neuroscience have found brain circuits that have evolved to support social and even altruistic behaviors, giving compassion a physical basis in our brains as well. These insights then set the stage for a shared interest in an altruistic compassionate society.